A youth-centred approach to improving engagement in HIV services: human-centred design methods and outcomes in a research trial in Kisumu County, Kenya - Maya Petersen; Laura K Beres; Elizabeth A Bukusi; Elvin H Geng; Ingrid Eshun-Wilson; Eliud Omondi Akama; Jayne Lewis Kulzer; Gladys Ontuga; Harriet Adhiambo; Sarah Bushuru; Edwin Nyagesoa; Joseph Osoro; et al. (BMJ Global Health, 2023)
Methods We applied an iterative, four-phased HCD process in Kenya that included: (1) systematic review of extant knowledge, (2) prioritisation of design challenges, (3) a co-creation workshop and (4) translation tables to pair insights with trial intervention adaptations. The co-creation workshop was co-led by youth facilitators employing participatory activities to inform intervention adaptations. Iterative data analysis included rapid thematic analysis of visualised workshop outputs and notes using affinity mapping and dialogue to identify key themes. We conducted a survey to assess workshop acceptability among participants.Results Twenty-two participants engaged in the 4-day workshop. Co-creation activities yielded recommendations for improving planned interventions (eg, message frequency and content; strategies to engage hard-to-reach participants), critical principles to employ across interventions (eg, personalisation, AYA empowerment) and identification of unanticipated AYA HIV treatment priorities (eg, drug holidays, transition from adolescent to adult services). We revised intervention content, peer navigator training materials and study inclusion criteria in response to findings. The youth-led HCD workshop was highly acceptable to participants.Conclusions Research employing HCD among youth can improve interventions preimplementation through empathy, youth-led inquiry and real-time problem solving. Peer navigation may be most influential in improving retention when engagement with young people is based on mutual trust, respect, privacy and extends beyond HIV-specific support. Identifying opportunities for personalisation and adaptation within intervention delivery is important for AYAs. Patient engagement interventions that target young people should prioritise improved transition between youth and adult services, youth HIV status disclosure, AYA empowerment and healthcare worker responsiveness in interactions and episodic adherence interruptions.